2021
DOI: 10.12820/rbafs.26e0206
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades na prática esportiva e de atividade física nas macrorregiões do Brasil: PNAD, 2015

Abstract: Estudos sobre desigualdades na prática de esporte e atividades físicas são uma importante ferramenta para embasar políticas públicas. Assim como abordagens de nível nacional, análises específicas de acordo com regiões se fazem necessárias. O objetivo deste estudo foi verificar as desigualdades em termos de sexo, cor da pele, área de residência e escolaridade na prática de esporte ou atividades físicas de acordo com as regiões do Brasil. Foram analisados os dados da investigação suplementar da Pesquisa Nacional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…This work found an inverse association between urban area residents and physical inactivity. These results are consistent with prior studies [86][87][88]. Urbanization greatly impacts the adoption of unhealthy lifestyles, such as sedentary behavior.…”
Section: Unhealthy Eatingsupporting
confidence: 92%
See 1 more Smart Citation
“…This work found an inverse association between urban area residents and physical inactivity. These results are consistent with prior studies [86][87][88]. Urbanization greatly impacts the adoption of unhealthy lifestyles, such as sedentary behavior.…”
Section: Unhealthy Eatingsupporting
confidence: 92%
“…Also, rural residents have lower income, which may contribute to lower levels of knowledge about the risks of physical inactivity and access to mechanisms for the practice of physical activity. Therefore, to mitigate inequalities in the practice of physical activity and sedentary behavior in urban and rural areas, public policies must be addressed [86][87][88].…”
Section: Unhealthy Eatingmentioning
confidence: 99%
“…In a review study, intrapersonal indicators were reported most frequently in adults and older adults in Brazil 97 , reinforcing the fact that there are few investigations at the social level. Although little investigated, the indicators of social status, among demographic aspects and education, were the only ones that showed inequality in the practice of PA 98 . As it is considered a domain with great potential for intervention, and because it contemplates the available time based on preferences and opportunities 95 , the categories found in the present study as leading Brazilians to be more active during leisure time corroborate the concept presented in the Physical Activity Guide for the Brazilians 95 .…”
Section: Environmentalmentioning
confidence: 99%
“…No que diz respeito ao movimento, pesquisas e inquéritos nacionais demonstram consideráveis desigualdades na prática de AF dos brasileiros, considerando seus quatro domínios e, em especial, nas exercidas no lazer. Homens, de cor da pele branca, com maiores níveis econômicos e de escolaridade, apresentam níveis de AF no tempo livre superiores, em comparação aos seus pares [31][32][33] , cenário de desigualdades que já demonstrou estar se ampliando com o estado pandêmico no país 34 . Logo, é de suma importância refletirmos o quanto é realmente eficaz e sensivelmente aceitável disseminar estas mensagens e promover a AF em todos os âmbitos, sem agregá-la algum sentido, em meio às discrepantes desigualdades do Brasil 35 .…”
Section: Resultsunclassified